Structure of Agency Formation Stages in Students: Consistency, Integrity, Formalization - Panov V.I; Kaptsov A.V (Moscow State University of Psychology and Education, 2021)
The article proposes a parallel-sequential formalized scheme for describing an ecopsychological model of agency formation through learning actions of students that includes seven stages. We were able to formulate mathematically based coefficients of consistency and integrity of the stages of agency formation in accordance with this model. It is empirically shown that in the samples of students (of universities: N1=79; M1=19.6; SD1=2.4, all females; of secondary vocational schools: N2=47; M2=16.6; SD2=0.68; all males; of schools, 9th grade: N3=45; M3=15.2; SD3=0.42, males - 43%; 11th grade: N4=52; M4=16.9; SD4=0.38, males - 38%) the model of the agency formation stages is described by a two- factor structure, depending on the motives and the objectives of learning activity. The composition of the factors of the agency formation stages is determined by the orientation on the perspective goals of learning activity which consist of the stages 'Critic', 'Master' and 'Creator', as well as on the current actual goals that includ the stages 'Observer', 'Apprentice' and 'Student'.